Pengenalan dan Demonstrasi Berbagai Teknik Pemisahan untuk Meningkatkan Pemahaman Siswa SMA Negeri 1 Batukliang Lombok Tengah Pada Mata Pelajaran Kimia Kelas XI - Gunawan, Erin Ryantin; Suhendra, Dedy; Handayani, Sri Seno; Aini, Diah Miftahul; Adiguna, Sya’ban Putra; Yanti, Sepia Dwi; Usiana, Shilan; Rischia, Amida (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2025)
This Community Service activity was conducted at SMA Negeri 1 Batukliang, Central Lombok, a senior high school offering a science (IPA) program and supported by the availability of a chemistry laboratory. The school faces several challenges, including a curriculum that has yet to incorporate real-life applications of chemistry, limited student understanding of chemical separation techniques, and inadequate laboratory facilities and infrastructure. This community service program aimed to introduce and demonstrate various separation techniques including extraction, distillation, and chromatography through interactive lectures, educational videos, and simple hands-on experiments, including processes like extraction, Soxhletation, and distillation. Through this activity, students not only gained theoretical knowledge but also practical experience in applying separation techniques and observing the products generated from these processes. This initiative aligns with the Sustainable Development Goals (SDGs), particularly in supporting quality education. The program is expected to enhance students’ scientific literacy and serve as an initial step toward raising awareness of the importance of chemistry in everyday life.